Pengaruh Potongan Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pelanggan Grab Food Mahasiswa Manajemen Unisma Malang - Wulan, Aisyah Dwi Fajar; Hidayati, Nur; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aims of this research are: 1) to analyze the simultaneous influence of price discounts and service quality on Grab Food customers' purchasing decisions, Unisma Management Students Class of 2020; 2) to analyze the effect of price discounts on Grab Food customers' purchasing decisions, Unisma Management Students Class of 2020; 3) to analyze the influence of service quality on Grab Food customers' purchasing decisions, Unisma Management Students Class of 2020. Using a sample of 60 UNISMA Management students class of 2020 as respondents, the research results show that 1) price discounts and service quality influence purchasing decisions simultaneously; 2) price discounts have a significant positive effect on purchasing decisions; 3) service quality has a significant positive effect on purchasing decisions. Keywords: Price Discounts, Service Quality, Purchasing Decisions.